Understanding student readiness for industrial internships: a qualitative exploration in vocational culinary education - Ni Nyoman Widya Adnyani; Basilius Redan Werang; Ni Wayan Sukerti (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2025)
This study aims to examine the underlying causes of low readiness among Grade XII culinary students at SMK Negeri 1 Sukasada in undertaking PKL. Employing a qualitative exploratory design, data were collected through in-depth interviews, observations, and document analysis involving students, teachers, school leaders, and industry partners. The study identifies a complex interplay of internal, institutional, and industry-related factors that collectively shape student readiness. Internal factors include fluctuating motivation, uneven technical competence, low self-confidence, and limited mental resilience. Institutional factors encompass gaps in PKL preparation, misalignment between curriculum and industry standards, insufficient intensity of practice-based learning, and limited mentoring mechanisms. Meanwhile, industry-related factors involve communication discontinuities, divergent expectations regarding work discipline and productivity, minimal pre-placement orientation, and highly demanding workplace cultures. Rather than operating independently, these factors interact dynamically, producing a cumulative effect that constrains students’ adaptive capacity and professional preparedness. The findings argue for a reconceptualization of PKL readiness not merely as an individual competency issue, but as a systemic alignment problem between vocational institutions and industry ecosystems. The study calls for structured co-design of curriculum and training modules with industry partners, the integration of resilience-building and workplace simulation into pre-PKL preparation, and the institutionalization of continuous feedback loops between schools and host industries. Such measures are crucial to strengthening vocational graduates’ transition from school to work and enhancing the overall effectiveness of PKL programs.